Prolegomena to the Development of an Inventory of Synsem Features for the Old English Verb - Javier E. Díaz Vera (Miscelánea: A Journal of English and American Studies, 2000)
Through the detailed analysis of the meaning definitions of different semantic sets of old English verbs and of their complementation patterns, I will propose a preliminary reconstruction of a basic set of synsem features, i.e. syntactic and semantic parameters which operate throughout the lexicon in the various areas of meaning. These features are divided into three basic types: obligatory, optional and contextual. Through the addition of a morphological component, T will propose some possible applications of Faber and Mairal’s (1988) semantic-syntactic model to the analysis of the Anglo-Saxon vocabulary.
Keywords: Semantic Syntax; FLM lexicon; lexical derivation; causation; case; impersonality; pragmatics